HCC-derived EGFR mutants are functioning, EGF-dependent, and erlotinib-resistant - Sueangoen, Natthaporn (Cell Biosci, 2020)
BACKGROUND: Epidermal growth factor receptor (EGFR) has emerged as an important therapeutic target. Overexpression of EGFR is frequently observed in hepatocellular carcinoma (HCC) and EGFR activation has been proven to be a potential determinant of primary resistance of HCC cells to sorafenib. In our previous study, we found 13 missense mutations in EGFR exon 19–23 from hepatocellular carcinoma (HCC) tissues, but the functions of these mutations have not been determined. This study aims to determine the kinase activity and sensitivity to erlotinib, a 1st-generation EGFR-tyrosine kinase inhibitor (TKI), of seven HCC-derived mutants (K757E, N808S, R831C, V897A, P937L, T940A, and M947T). RESULTS: Using transduction of pBabe-puro retroviral vector with or without EGFR, we constructed and determined the function of EGFRs in NIH-3T3 cells stably harboring each of the seven mutants, as well as the erlotinib-sensitive L858R-mutant, the erlotinib-resistant T790M-mutant, and EGFR wild type (WT). Our results indicate that the seven mutants are functioning, EGF-dependent, EGFRs. Cells harboring six of the seven mutants could generate some level of EGFR phosphorylation in the absence of EGF, indicating some constitutive kinase activity, but all of the seven mutants remain primarily EGF-dependent. Our results demonstrate that erlotinib induces differential degree of apoptosis and autophagy among cells harboring different EGFRs: complete apoptosis and autophagy (cleavage of both caspase-3 and PARP, and marked LC3-II increment) in L858R-mutant; partial apoptosis and autophagy (only cleavage of caspase-3, and moderate LC3-II increment) in WT and HCC-derived mutants; and no apoptosis and minimal autophagy (no cleavage of caspase-3 and PARP, and minimal LC3-II increment) in T790M-mutant. The seven HCC-derived mutants are erlotinib-resistant, as treatment with erlotinib up to high concentration could only induce partial inhibition of EGFR phosphorylation, partial or no inhibition of AKT and ERK phosphorylation, and partial apoptosis and autophagy. CONCLUSION: The seven HCC-derived EGFR mutants in this study are functioning, EGF-dependent, and erlotinib-resistant. Erlotinib induces differential degree of apoptosis and autophagy among cells harboring different EGFRs. The degree of inhibition of EGFR phosphorylation by erlotinib is the determining factor for the degree of apoptosis and autophagy amongst cells harboring EGFR mutants. This study paves the way for further investigation into the sensitivity of these HCC-derived mutants to the 3rd-generation irreversible EGFR-TKI, osimertinib.